THE IMPLEMENTATION OF MARKETING STRATEGY WITH BUZZER INSTAGRAM IN KARAMAYA ENTERTAINMENT - I Wayan Ary Sugiatha; I Nyoman Rajin Aryana; I Gusti Agung Mas Komala Sari (Politeknik Negeri Bali, 2018)
This research aimed at knowing the strengths, weaknesses, threats, and opportunities of instagram buzzer implemenented by marketing event department at Karamaya Entertainment. In this research, data analysis technique used was qualitative descriptive analysis technique and SWOT analysis with data collection method using obsevation technique, interview, and documentation to get data. The result of SWOT analysis shows that marketing strategy by instagram buzzer was in accordance with the expectation to be applied to Karamaya Entertainment. The SWOT analysis performed from instargram buzzer on Karamaya Entertainment was as follows; first, Strengths in promoting an event can drag audiance from a personal account instagram buzzer. Second, weaknesses of instagram buzzer system require buzzer to update any post on instagram. Third, Threats caused by online system disruptions which impact on buzzer performance. Fourth, instagram buzzer opportunities become a trend of young people in doing business online or promoting the event with the image or short video content uploaded into the instagram buzzer. The results of this study can be proven by the number of audience attending every event of Karamaya Entertainment from August 2017 to date exceeds set by the client using instagram buzzer.